I diritti umani e il sesso "debole" (Società e diritti, 2020)
According to Edward B. Tylor, culture, or civilization, understood in its broad ethnographic sense, is that complex whole that includes knowledge, beliefs, art, morals, law, customs and any other competence or habit acquired by man as a member of society. From this approach it is easy to deduce that culture is a key point for every population, since over time it allows you to define a people, making it unique and equal only to itself. Equally fundamental is the tradition which consists in passing down, from generation to generation, those customs proper to the culture of a people which - representing an essential aspect of cultural identity and belonging to the tradition of some populations - can lead to a serious violation of human rights understood in the most common sense. In this short essay of mine I will try instead to take a different look at the motivations that perpetuate these practices by analyzing how these are perceived by the populations that pass them down. Always adopting a sociological key, I will try to propose the concept of "agency" as a central approach and tool for a deeper and lasting change towards an understanding, and perhaps also an acceptance, of these "our" human rights by those populations with an exquisitely traditional imprint.